DINAMIKA PENYELESAIAN SENGKETA LIMA DESA DARI ROKAN HULU KE KABUPATEN KAMPAR PROVINSI RIAU TAHUN 2010-2017 - Fransio, Karldo; Marta, Auradian (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Regional expansion is basically an effort to create an effective and efficient government, as well as effective in order to realize the acceleration of improving people's welfare. Thus, the development and development of regional autonomy today is able to develop initiatives to foster new forces in society. In addition, to bring services closer to the community and create more effective supervision control. However, in expansion, of course there are disputes. One of the disputes over the boundaries of the Regency is the Five Villages Dispute between Kampar Regency and Rokan Hulu Regency. This dispute came to the surface when there was a lawsuit letter from the Chairman of the Village Consultative Body (BPD) of Five Villages, Tapung Hulu District, Kampar Regency on May 20, 2010. This study aims to find out what causes the conflict between Kampar Regency and Rokan Hulu Regency and to find out the legal aspects of dispute resolution in five villages between Kampar Regency and Rokan Hulu Regency. The research method used is normative juridical. That is, by collecting primary legal materials, primary legal materials are legal materials that have authority (authoritative). The results of this study show that the Supreme Court's decision only cancels the Decree of the Minister of Home Affairs and there is no decision stating that five villages are included in the Kampar Regency area. After the issuance of this Supreme Court decision, the status of five villages is still floating because in Article 4 of Law 53 of 1999 it is still stated that Rokan Hulu Regency has seven sub-districts, one of which is Kunto Darussalam District. Likewise, Permendagri No. 56 of 2015 which included five villages in the Kampar Regency area can still be sued. So, the settlement of the dispute in five villages with the issuance of Permendagri No. 56 of 2015 does not solve the root of the problem. Keywords: Dynamics, Dispute Resolution, Five Village Disputes